The Moderating Role of Anticipated Regret and Product Involvement on Online Impulsive Buying Behavior - Li, Bin; Hu, Minqi; Chen, Xiaoxi; Lei, Yongxin (Frontiers in Psychology, 2021)
Online impulsive buying behavior has drawn an increasing amount of attention from researchers and marketers as well, however, little research has explored how cognitive aspect and emotional aspect effect online impulsive buying together. The study examines the role of product involvement (cognitive aspect) and anticipated regret (emotional aspect) on consumer’s online impulsive buying behavior. The results indicate that consumers who experienced downward anticipated regret showed more online impulsive buying behavior than those who experienced upward anticipated regret. Moreover, anticipated regret moderates the relationship between product involvement and online impulsive buying behavior, for participants who experienced downward anticipated regret showing more online impulsive buying behavior than those who experienced upward anticipated regret in low product involvement group, but there is no differential between downward and upward anticipated regret in high involvement product group. These findings suggest that anticipated regret help consumers make more deliberative online shopping choices. The implications for both future research and online comsumers are discussed.